Douglas Kammen and Katharine Mcgregor, eds. The Contours of Mass Violence in Indonesia, 1965–1968. Kyoto CSEAS Series on Asian Studies 7. Singapore: National University of Singapore Press in association with Kyoto University Press, 2013. 276 pp. - Curaming, Rommel A. (Archīum Ateneo, 2014)
Excerpt: Despite its appalling magnitude, the 1965–1968 mass killings in Indonesia have been at the fringes of international historical imagination. While it has received an increased attention in the past years, particularly with recent Oscar nomination for Oppenheimer’s documentary !e Act of Killing, it pales in comparison with other gruesome cases such as Cambodia’s “killing !elds” and Rwanda’s genocide, prompting some people to dub it as the “forgotten Holocaust.” The number of serious studies has been very limited with Java and Bali as the main focus. The volume under review here is a very notable contribution to our understanding of this complex set of events and their lasting repercussions.